A-17 Self-Generation Improves Prospective Memory Performance in Individuals with Moderate–Severe Traumatic Brain Injury. (30th August 2021) - Weber, Erica; Hirst, Dana L; Yi, Nancy; Li, Yanqi Ryan; Loft, Shayne; Woods, Steven P; Chiaravalloti, Nancy D
Abstract: Objective: Self-generation has long been studied in healthy adults as a method to improve encoding of new information. The present study applied this strategy to prospective memory (PM; the ability to remember future intentions) in individuals with traumatic brain injury (TBI). Method: Participants included 17 healthy adults and 34 individuals with moderate–severe TBI, who were at least one year post-injury and impaired encoding on a test of verbal learning. Participants completed a 15-minute computer-based lexical decision task in which PM trials were embedded. Following a baseline block of 100 lexical decision trials, participants completed 2 blocks with 5 p.m. targets each. PM targets were learned in a didactic or self-generated fashion using semantically-related word pairs, counterbalanced for order effects. Results: MANOVAs were conducted for PM accuracy and recognition, with performance in the didactic and self-generation conditions as within-subjects variables and diagnostic group as the between-subjects variable. Only the within-subjects variables were significant [PM accuracy: F(1, 49) = 5.228, p = 0.027; PM recognition: F(1, 49) = 7.226, p = 0.010]. Within the TBI sample, paired t-tests demonstrated significantly improved PM accuracy [t(33) = −2.069, p = 0.046, Hedge's g = 0.38] and PM target recognition [t(33) = −2.458, p = 0.019, Hedge's g = 0.52] under self-generated compared to didactic conditions. Conclusion: Results indicate that self-generation is an efficacious strategy to improve PM in individuals with moderate–severe TBI and encoding deficits. The lack of interaction suggests that the generation effect is robust enough to provide comparable benefit to both individuals with significant neurocognitive deficits as well as healthy adults. Future efforts should explore the incorporation of self-generation in cognitive rehabilitation protocols for PM in neurologic populations.